Awareness about proper use of sunscreen in people of color: A Jordanian‐based survey. (29th August 2019) - Al‐Qarqaz, Firas; Marji, Maha; Bodoor, Khaldon; Al ALshiyab, Diala; Muhaidat, Jihan; Al Ghamdi, Saleh
Abstract: Introduction: The use of sunscreen is an important preventive measure against skin cancer and treatment for other skin conditions. There is evidence pointing to lack awareness and misconceptions regarding use of Sunscreen. This is especially evident in populations with skin of color (POC). Methods: This is a cross‐sectional study of 2000 individuals. A structured questionnaire was designed to collect data on general knowledge and use of sunscreen as well as reasons for stopping use of sunscreen. Results: The results of this study indicate a clear deficiency in the use and knowledge about sunscreen among Jordanians. Females are using sunscreen more than males. However, the use of sunscreen is inadequate in many aspects including timing of application, frequency of use, and amount used among other things. There is an obvious lack of knowledge about sunscreen as shown by lack of awareness about benefits of use in various times of the year, use in children, use for all skin types, and several misconceptions among other knowledge gaps. Main reasons for stopping sunscreen include side effects, cost, and being not suitable for skin. Awareness about sunscreen can be improved by proper counseling by healthcare professionals and utilization of various media platforms. Conclusions: The use of sunscreen is inadequate in this population of color (POC). Lack of proper counseling, failure to read use instructions can contibute to inadequate use of sunscreen. Risks and benefits of sunscreen should be explained by medical professionals. The media should be more utilized to disseminate such knowledge.